2015
DOI: 10.1002/ajpa.22810
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term impact of developmental stress. Evidence from later medieval and post‐medieval London (AD1117–1853)

Abstract: Macroscopic hypoplasia represent short periods of stress during infancy/early childhood which did not disrupt future investments in growth or cause long-term damage to health. Small TR diameters represent chronic stress during late childhood/early adolescence which resulted in greater susceptibility to infections and increased risk of mortality. These interactions were influenced by sex and socioeconomic status, suggesting that socioeconomic circumstances in both childhood and adult life could influence exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 58 publications
3
35
1
Order By: Relevance
“…Additional studies use factors such as the timing of stress events or evidence for developmental stability as measures of exposure to early life stress and the resultant consequences on life history. Transverse diameter of the vertebral neural canal was associated with adult mortality in low status males and high/middle status females in Medieval and Historic London, while no mortality risk was found in high status males and low status females . The results suggest variation in the physiological constraints following early life adversity may occur according to economic status or gendered identities.…”
Section: Bioarchaeological Approachesmentioning
confidence: 81%
“…Additional studies use factors such as the timing of stress events or evidence for developmental stability as measures of exposure to early life stress and the resultant consequences on life history. Transverse diameter of the vertebral neural canal was associated with adult mortality in low status males and high/middle status females in Medieval and Historic London, while no mortality risk was found in high status males and low status females . The results suggest variation in the physiological constraints following early life adversity may occur according to economic status or gendered identities.…”
Section: Bioarchaeological Approachesmentioning
confidence: 81%
“…Various studies on the distribution of LEH showed an association with decreased lifespan (Goodman, 1989;Goodman and Armelagos, 1989;Duray, 1996;Steckel, 2005;Boldsen, 2007;Armelagos et al, 2009). However, the opposite relationship was also found (Amoroso et al, 2014;Watts, 2015) and thus the relationship between early insults and premature mortality is still to be fully understood. Despite the proportion of affected individuals being slightly higher at a younger age, this difference was not significant (Fisher's exact test, p value=0.8885).…”
Section: Discussionmentioning
confidence: 97%
“…In the archeological sample from Santarém, there are no spoil in the graves because the Islamic burial ritual promotes equality in death, which invalidates any associations with social classes (Matias, 2009b(Matias, , 2009c. Yet, other studies on the association of LEH and longevity have reported no relationship with socioeconomic status (Duray, 1996;Watts, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, even if the number of individuals originally buried in a particular archaeological site was quite large, it might only be possible to excavate a small proportion of them. For example, the excavated assemblage from the medieval East Smithfield cemetery from London, which has been used for various studies reported in AJPA (e.g., DeWitte, ; Kendall, Montgomery, Evans, Stantis, & Mueller, ; Margerison & Knüsel, ; Watts, ), represents only about 25% of the original cemetery. In paleodemography, sample sizes sufficiently large for interpretable analyses are often obtained by pooling data temporally, geographically, or along some other variable.…”
Section: Problems With Demographic Datamentioning
confidence: 99%